1968
DOI: 10.1136/bmj.3.5615.424
|View full text |Cite
|
Sign up to set email alerts
|

Drugs left at home by psychiatric inpatients.

Abstract: Robin, Brooke, and Freeman-Browne (1968) reported that during the years 1952-64 an increasing proportion of suicides in the county borough of Suuthend were known to have had contact with the psychiatric services of the town at some time in their lives, often within three months of suicide. Of 92 patients who later committed suicide 72 (78 %) were diagnosed as suffering from affective disorders when first psychiatrically examined, and the great majority (79%) of those with a psychiatric contact) were at some ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The availability of barbiturates and other prescription drugs, however, has been seen as an added factor making impulsive suicide more likely (Lester, 1972). Robin and Freeman‐Browne (1968) noted that the majority of attempted suicides are released into a home environment where abundant quantities of lethal methods exist. Barraclough, Nelson, Bunch and Sainsbury (1971) have made a similar point.…”
mentioning
confidence: 99%
“…The availability of barbiturates and other prescription drugs, however, has been seen as an added factor making impulsive suicide more likely (Lester, 1972). Robin and Freeman‐Browne (1968) noted that the majority of attempted suicides are released into a home environment where abundant quantities of lethal methods exist. Barraclough, Nelson, Bunch and Sainsbury (1971) have made a similar point.…”
mentioning
confidence: 99%
“…A more personal consequence of drug defaulting relates to the enormous economic wastage involved (Curdiner (1968) ) ; and a less quantifiable factor is the potential hazard to health posed by cupboards stocked with unused and unidentifiable tablets accumulated over the years. The substantial significance of such findings was iUust ated in a British investigation in which unused medication in the homes of psychiatric patients was examined and it was found that those with suicidal risk often had such supplies available (Robin & Freeman-Browne (1968) ).…”
Section: Introductionmentioning
confidence: 99%